Exploring the complex relationship between theory and methodology when studying mathematics-related motivation - Suriakumaran, Neruja; Hannula, Markku S. (LUMAT-B: International Journal on Math, Science and Technology Education, 2024)
A well-founded research paradigm is essential for gaining acceptable research results. To highlight the associations between ontology, epistemology, and methodology, we refer to an investigation on German and Finnish students’ motivation in mathematics classroom. We identified four kinds of mathematics-learning orientations from German and Finnish 9th graders using latent class analysis. When comparing the profile outputs, discriminant analysis (quantitative approach) revealed no convincing differences. The coordination analysis method (qualitative approach) in turn reflected that different foci within German and Finnish mathematics curricula exist. The findings highlight to identify and specifically tailor the methodology according to the ontological and epistemological principles of theory.